Raoul Walsh : the true adventures of Hollywood's legendary director - Moss, Marilyn Ann (Screen classics (Lexington, Ky.), 2011)
Raoul Walsh (1887-1980) was known as one of Hollywood's most adventurous, iconoclastic, and creative directors. He carved out an illustrious career and made films that transformed the Hollywood studio yarn into a thrilling art form. Walsh belonged to that early generation of directors-along with John Ford and Howard Hawks-who worked in the fledgling film industry of the early twentieth century, learning to make movies with shoestring budgets. Walsh's generation invented a Hollywood that made movies seem bigger than life itself. In the first ever full-length biography of Raoul Walsh, author Marilyn Ann Moss recounts Walsh's life and achievements in a career that spanned more than half a century and produced upwards of two hundred films, many of them cinema classics. Walsh originally entered the movie business as an actor, playing the role of John Wilkes Booth in D.W. Griffith's The Birth of a Nation (1915). In the same year, under Griffith's tutelage, Walsh began to direct on his own. Soon he left Griffith's company for Fox Pictures, where he stayed for more than twenty years. It was later, at Warner Bros., that he began his golden period of filmmaking. Walsh was known for his romantic flair and playful persona. Involved in a freak auto accident in 1928, Walsh lost his right eye and began wearing an eye patch, which earned him the suitably dashing moniker "the one-eyed bandit." During his long and illustrious career, he directed such heavyweights as Humphrey Bogart, James Cagney, Errol Flynn, and Marlene Dietrich, and in 1930 he discovered future star John Wayne